A evolução e o impacto dos indie games: uma analise sobre No man’s sky - Hall, Denner Mark (Universidade Federal de São Carlos, 2017)
The independent cultural manifestation of the digital games, can be for many, a recent phenomenon, that has been brought by the digital distribution and the increasing number of platform; from smartphones and tablets to the videogames of the latest generation. However, delving deeper into the historical bias of independent production we can notice the first experimental manifestation from this medium, outside of the commercial means. Experimentations that celebrate the unrestricted access to computers outside scientists, experimentation that made possible the formation of communities connected online before the advent of the internet, that created ways for hobbyists, amateurs, and new game designers explored a rich means of expression in this medium. Therefore, this study was made in order to obtain an understanding of the evolution in independent production in video games and its complex unfolding. These unfolding allowed that indie games to have different impacts. The first impact analyzed here is the growth of the Brazilian game production, the importance of a low-cost format of production moved by creativity and the shaping of a strong independent movement in Brazil. The other impact analyzed is the recurrent phenomenon that blurs the line between mainstream and indie. This work aimed to study this phenomenon under the lens of the complex game No Man’s Sky, made by a small and unknown independent studio called Hello Games. Hello Games became infamous in the game industry due to the problematic launch of No Man’s Sky, one of the most anticipated titles of 2016 that failed to meet the expectations of the players. It was then analyzed the artistic approach, narrative, interactivity and technical complexity of No Man’s Sky in other to comprehend how a small studio was capable of creating 18 quintillion planets.
The evolution and the impact of the indie games: an analysis about No man's sky
Keywords: Jogos digitais; Produção independente; Economia criativa; Geração procedural; Digital games; Independent production; Creative economy; Procedural generation; Juegos digitales; Producción independiente; Economía creativa; Generación procedural; LINGUISTICA, LETRAS E ARTES::ARTES